Computer simulation of diffractive imaging lenses using hyperspectral images - S.I. Kharitonov; V.A. Fursov (Компьютерная оптика)
We offer a computer technology for modeling a process of optical imaging with a diffractive imaging lens. The central idea of the technology is to evaluate the quality of the optical system by matching the input and output images against criteria adopted in image processing. For this purpose, same-resolution hyperspectral images are fed to the input and generated at the output. Thanks to the large number of spectral components, a fairly accurate reproduction of the effects associated with the dependence of the refractive index on the wavelength is ensured. To compare input and output images in terms of PSNR (peak signal-to-noise ratio), standard three-component RGB images are "assembled" using standard matching functions over the entire optical range. Results of the study of the dependence of the PSNR indicator on the main parameters of the optical system are given: focal length, linear aperture and the number of diffraction orders taken into account.